2016
DOI: 10.4236/aim.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, Stress Tolerance and Plant Growth Promoting Characteristics of Rhizobial Isolates from Selected Wild Legumes of Semiarid Region, Tirupati, India

Abstract: Rhizobia are vital for nitrogen input, fertility of soil and legume plant growth. Knowledge on rhizobial diversity from arid and semiarid areas is important for dry land agriculture in the context of climatic change and for economic utilization. This study provides morphological, biochemical, stress tolerance and plant growth promoting characteristics of fifteen rhizobial isolates from the nodules of same number of wild legumes and one isolate from cultivated Arachis hypogea from semi-arid region, Tirupati. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Our results concerning the effect of inoculation by the tested bacteria on Acacia cyanophylla seed germination are consistent with several studies [26,41,44] which claimed that the use of PGPR specifically IAA producing bacteria might have a significant effect on increasing seed germination rate and promoting plant growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results concerning the effect of inoculation by the tested bacteria on Acacia cyanophylla seed germination are consistent with several studies [26,41,44] which claimed that the use of PGPR specifically IAA producing bacteria might have a significant effect on increasing seed germination rate and promoting plant growth.…”
Section: Discussionsupporting
confidence: 92%
“…The variation in IAA production by different rhizobial isolates and the influence of cultural conditions on IAA produced amount has been reported by many authors [39][40][41]. The variation in IAA production is may be due to variation in L-Trp utilization by each isolate.…”
Section: Discussionmentioning
confidence: 93%
“…They were purified and propagated using YMA medium (Yeast Mannitol Agar). The inoculants were propagated using YMA medium without agar (Bhargava et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Florentino et al (2010) also reported that rhizobia isolated from cowpea were able to tolerate temperatures of 28°C and 36°C, and none of the strains grew at 45°C. The higher temperature is reported to alter the permeability of the membrane and leading to the denaturation of enzymes/ proteins causing the death and/or poor growth of the rhizobia (Bhargava et al, 2016).…”
Section: Temperature Tolerancementioning
confidence: 99%